2007
DOI: 10.1080/07315170701313716
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties and Relaxor Behavior of PIN Based System

Abstract: Several compositions in the two PIN based systems (1-x)Pb(In 0.5 Nb 0.5 )O 3 -(x)PbTiO 3 and (0.8-x)Pb(In 0.5 Nb 0.5 )O 3 -(x)PbTiO 3-0.2BaTiO 3 (x = 0.0, 0.1, 0.2 and 0.3) were synthesized via the wolframite method. Dielectric properties were measured in the frequency range between 100 Hz and 100 kHz and were analyzed for understanding relaxor behavior in the system. The temperature dependence of the dielectric properties was analyzed by studying the deviation from the Curie-Weiss law while the frequency depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
(22 reference statements)
1
9
0
Order By: Relevance
“…The dielectric properties of the compositions with x 6 0.3 exhibited a diffuse phase transition with dielectric peak broadening [24]. As listed in Table 1, the high value of dielectric constant under stress-free condition at room temperature is obtained in ceramic composition with x = 0.4, because of its vicinity to the morphotropic phase boundary (MPB) of PIN-PT system, as reported earlier [14,21,22].…”
Section: Resultsmentioning
confidence: 50%
See 2 more Smart Citations
“…The dielectric properties of the compositions with x 6 0.3 exhibited a diffuse phase transition with dielectric peak broadening [24]. As listed in Table 1, the high value of dielectric constant under stress-free condition at room temperature is obtained in ceramic composition with x = 0.4, because of its vicinity to the morphotropic phase boundary (MPB) of PIN-PT system, as reported earlier [14,21,22].…”
Section: Resultsmentioning
confidence: 50%
“…More information on the above mentioned characteristics can be found in previous publications [21,22]. By X-ray diffraction method, the phase and structural information of the PIN-PT ceramics was established [22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All compositions show broad maximum of the dielectric constant. More details of the dielectric properties underlying frequency and their relaxor behavior have been reported in our previous work [25]. The dielectric constant maxima (ε m ) slightly increase with the composition of x = 0.1 and then drastically increase with more PT concentrations.…”
Section: Resultsmentioning
confidence: 92%
“…In the disordered state, PIN reveals a relaxor behavior and a broad maximum of dielectric permittivity in the vicinity of 340 K. In the ordered state, PIN is an antiferroelectric with the tem perature of the maximum in ε close to 440 K. There are several review papers reporting on studies of the dielectric properties of solid solutions of the relaxor ferroelectric PIN and the normal ferroelectric PT [6,7]. As seen from the phase diagram of these com pounds [7], the compositions lying close to the MPB (x ≈ 0.37) have the Curie temperature above 520 K. The dielectric studies of the compositions lying close to the MPB have revealed the cubic to tetragonal and tetragonal to rhombohedral (T tr ) phase transitions, which resemble those observed in PMN-xPT and PZN-xPT.…”
Section: Introductionmentioning
confidence: 97%